National and international legal solutions for the transition to digitalization of transport and agricultural engineering of Kazakhstan - Sarsembayev, M.A.; Sarsenova, S.N.; Karazhan, B.S. (Bulletin of the Karaganda University “Law Series”, 2021)
The article shows that the development of the proposed topic on solving legal, organizational and managerial problems on digitalization and electric mobility in the field of transport and agricultural engineering can be useful for the Ministry of Industry and Infrastructure Development of the Republic of Kazakhstan, responsible for the development of mechanical engineering in the country, development and adoption of the new Kazakhstan law “On Industrial Policy” and other laws, through which transport and agricultural engineering will give a powerful impetus to the “development of a qualitatively new national creative industry”. The authors proceed from the need to develop own agricultural machinery, and to buy abroad only those agricultural machines that Kazakhstan does not produce. The authors believe that the adoption in Kazakhstan of such laws as “On the introduction of digitalization, artificial intelligence devices, automation in the production processes of transport and agricultural engineering”, “On the launch of mass production of electric and unmanned vehicles and agricultural equipment”, “On the creation of an industry for the disposal of obsolete transport and agricultural equipment” will contribute to the introduction of digitalization of transport and agricultural machinery in the republic. Kazakhstan's membership in the Eurasian Economic Union (EAEU), UNIDO (UN Industrial Development Organization) creates opportunities and at the same time high requirements for digital competitiveness, both in the domestic and global markets. In this regard, the role of state regulation of the issues of digitalization of the economy, industry, and mechanical engineering becomes extremely important.